2015
DOI: 10.1038/ja.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel endophenaside antibiotics produced by Kitasatospora sp. MBT66

Abstract: Actinomycetes are a major source of bioactive secondary metabolites and are a focal point in the search for novel antimicrobial compounds that are needed to combat multidrug-resistant pathogens. Here, we report the discovery of several novel phenazine-type antibiotics produced by Kitasatospora sp. MBT66. These include the novel glycosylated endophenazines A-E (1-5), together with N-prenylated endophenazine F1 (6). Compounds 1 and 3 contain a 2'-O-methylation of the sugar moiety, which is rare in nature and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…The producing strain, compound name, activities of the compounds, reported by year, are shown in Table 3. 1,10,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Setamycin possesses antitrichomonal and antifungal activities. Phosalacine possesses herbicidal activity.…”
Section: Diversity Of Biological Active Compounds Produced By Kitasatmentioning
confidence: 99%
“…The producing strain, compound name, activities of the compounds, reported by year, are shown in Table 3. 1,10,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Setamycin possesses antitrichomonal and antifungal activities. Phosalacine possesses herbicidal activity.…”
Section: Diversity Of Biological Active Compounds Produced By Kitasatmentioning
confidence: 99%
“…By studying all known species of this genus such as K. cystarginea (Kusakabe and Isono, 1988); K. cochleata and K. paracochleata (Nakagaito et al, 1992;Zhang et al, 1997); Kitasatospora kimorexae 90- GT-302 (yeo et al, 1994) K. cheerisanensis (Chung et al, 1999); K. cineracea and K. Niigatensis (Tajima et al, 2001) and Kitasatospora sp. MBT66 (Wu et al, 2015) and Takahashi (2017) confirmed that the four isolates differ in many physiological and phenotypic properties. The most important characteristic of these species is that they grow on alkaline media better than their growth on neutral media and that their physiological properties appear better on alkaline media than in neutral media and therefore can be considered new species of the Kitasatospora.…”
Section: It Is Clear From Tablementioning
confidence: 66%
“…130, methyphenazine-1-carboxylate, was isolated as a metabolite from S. luteoreticuli in 1971. 23) Recently, No. 130 was reported as a metabolite produced by Pseudomonas chlororaphis and strains of the genus Kitasatospora; moreover, the antifungal and anti-Gram-positive-bacterial activities of No.…”
Section: Resultsmentioning
confidence: 99%